Apostolic tradition : a new commentary - Bradshaw, Paul F. (Collegeville, Minnesota : Liturgical Press Academic, 2023)
"A commentary based on the 2011 Ethiopic text of the Apostolic Tradition of Hippolytus of Rome, suitable for beginner and scholar alike"--
Includes bibliographical references and index.
Keywords: Hippolytus, -- Antipope, -- approximately 170-235 or 236.; Canon law -- Early church, ca. 30-600.; Church history -- Primitive and early church, ca. 30-600 -- Sources